2011
DOI: 10.1111/j.1365-313x.2011.04533.x
|View full text |Cite
|
Sign up to set email alerts
|

Root hair‐specific expansins modulate root hair elongation in rice

Abstract: SUMMARYRoot hair growth requires intensive cell-wall modification. This study demonstrates that root hair-specific expansin As, a sub-clade of the cell wall-loosening expansin proteins, are required for root hair elongation in rice (Oryza sativa L.). We identified a gene encoding EXPA17 (OsEXPA17) from a rice mutant with short root hairs. Promoter::reporter transgenic lines exhibited exclusive OsEXPA17 expression in root hair cells. The OsEXPA17 mutant protein (OsexpA17) contained a point mutation, causing a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(66 citation statements)
references
References 40 publications
(52 reference statements)
3
63
0
Order By: Relevance
“…Three expansins, which are encoded by HvEXPB1 (Kwasniewski and Szarejko, 2006), OsEXPB5, and OsEXPA17 (Won et al, 2010;ZhiMing et al, 2011), have been proven to be involved in RH initiation and elongation. Mutant analysis showed that the HvEXPB1 transcript is present in the root but not in the shoot (Kwasniewski and Szarejko, 2006).…”
Section: "Tis Within Ourselves That We Are Thus or Thus": Elongation mentioning
confidence: 99%
See 1 more Smart Citation
“…Three expansins, which are encoded by HvEXPB1 (Kwasniewski and Szarejko, 2006), OsEXPB5, and OsEXPA17 (Won et al, 2010;ZhiMing et al, 2011), have been proven to be involved in RH initiation and elongation. Mutant analysis showed that the HvEXPB1 transcript is present in the root but not in the shoot (Kwasniewski and Szarejko, 2006).…”
Section: "Tis Within Ourselves That We Are Thus or Thus": Elongation mentioning
confidence: 99%
“…A rice line that produced RHs that were 70% shorter than those of the wild type has been shown to harbor a single nucleotide variant for OsEXPA17. This gene is specifically transcribed in the RH, and its promoter also includes an RH-specific ciselement (ZhiMing et al, 2011). The mutant phenotype proved to be partially reversible by constitutively expressing OsEXPA30, which is a gene encoding an RH-specific expansin.…”
Section: "Tis Within Ourselves That We Are Thus or Thus": Elongation mentioning
confidence: 99%
“…For instance, CSLF6, a putative cellulose-like synthase family member, is required for rice primary and adventitious root development through a phosphate accumulation-dependent pathway (Jin et al, 2015). Rice expansin genes, including OsEXPA8, OsEXPA17, and OsEXPB5, are reported to modulate root development (Won et al, 2010;ZhiMing et al, 2011;Ma et al, 2013). In addition, CESAs (cellulose synthases) are delivered to cell plate and deposit cellulose via phragmoplast-associated vesicles during cell division in Arabidopsis root (Miart et al, 2014).…”
Section: Wox11 Recruits Ada2/gcn5 To Establish Gene Expression Programentioning
confidence: 99%
“…However, the number of reports showing that repression of expansin gene expression actually leads to a repression in growth is surprisingly limited (Cho and Cosgrove, 2000;Zenoni et al, 2004;ZhiMing et al, 2011). Part of the reason for this is that expansins are encoded by relatively large gene families, leading to potential problems of genetic redundancy when single gene members are mutated or their expression is repressed .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this potential complication, reports have been made in which a clear growth phenotype resulted from the suppression of a single expansin gene (Cho and Cosgrove, 2000;Choi et al, 2003;Zenoni et al, 2004;ZhiMing et al, 2011). These investigations have targeted root hairs and petals in dicots and the mesocotyl and coleoptile in monocots, but to date, only one experiment relating the suppression of expansin gene expression to leaf growth has been reported.…”
mentioning
confidence: 99%